Efficient Buchwald–Hartwig–Migita Cross‐Coupling for DNA Thioglycoconjugation. Issue 8 (16th January 2018) - Probst, Nicolas; Lartia, Rémy; Théry, Océane; Alami, Mouâd; Defrancq, Eric; Messaoudi, Samir
Abstract: An efficient method for the thioglycoconjugation of iodinated oligonucleotides by Buchwald–Hartwig–Migita cross‐coupling under mild conditions is reported. The method enables divergent synthesis of many different functionalized thioglycosylated ODNs in good yields, without affecting the integrity of the other A, C, and G nucleobases. Abstract : Sweet ODNs : A new strategy for the post functionalization of ODNs is presented. Using Pd‐catalysis, the strategy enabled the synthesis of various thioglycosylated ODNs.